The Multiplication Operator from F(p,q,s) Spaces to nth Weighted-Type Spaces on the Unit Disk - Yongmin Liu; Yanyan Yu (Journal of Function Spaces and Applications)
Let H(𝔻) be the space of analytic functions on 𝔻 and u∈H(𝔻). The boundedness and compactness of the multiplication operator Mu from F(p,q,s),(or  F0(p,q,s)) spaces to nth weighted-type spaces on the unit disk are investigated in this paper.